Study on the operation strategies and carbon emission of heating systems in the context of building energy conservation - Jiaying Teng; Hang Yin; Pengying Wang (Energy Science & Engineering, 2023)
Abstract Coal‐fired thermal power must be flexible to enable the grid absorption of inconsistent photovoltaic (PV) and wind power. Combined heat and power (CHP) coal‐fired plants are the primary source for district heating systems. This paper uses a 330 MW subcritical CHP unit as an example to carry out the study. With the promotion of building energy efficiency, when the thermal index is reduced to below 20 W/m2, the low‐load operation of CHP can meet the wind power and PV feed‐in demand and guarantee residential heating without the need for flexibility modification. Meanwhile, more renewable energy generation can reduce carbon emissions from the power supply, further contributing to reducing carbon emissions from buildings. The impacts of different envelope parameters and supplementary heat sources on building carbon emissions are also studied. The conclusion shows that the degree of their impact on carbon emissions ranks as ESMs (energy supply modes) > Factor D (infiltration N50) > Factor A (external wall heat transfer coefficient) > Factor C (window heat transfer coefficient) > Factor B (roof heat transfer coefficient). When the building's heating energy consumption gradually decreases, the distributed heat pump unit can replace the coal‐fired boiler to supply the peak heat load demand. In the future, China's district heating systems can be gradually changed from the current CHP and coal‐fired boilers to CHP and distributed heat pumps.